MANAJEMEN PENDAMPINGAN GURU UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU-GURU MATA PELAJARAN SEKOLAH MENENGAH PERTAMA DI KOTA BANDUNG - Asep Zuhara Argawinata (JURNAL MITRA SWARA GANESHA, 2016)
ABSTRACT This study questioned the extent of the effectiveness of teachers mentoring management to improve pedagogical competence and professional for SMTP science teachers in West Java, especially in Bandung district. The results of this study would be useful for improving the quality and competence development of the science teachers. This research uses a causal comparative method with quota sampling technique. The focus of the problem is the management effectiveness of mentoring curriculum in 2013. The research data were be collected through questionnaires. Then the data were analyzed quantitatively by calculating the mean and standard deviation, t-test, and correlation. The study results indicate that there is a significant difference in quality pedagogical competence and professional competence amongÂ  teachers of SMP/S following the manajemen mentoring of teachers and they are not. The conclusion is that montering Â management of the teacher is effective in improving the quality of pedagogical and professional competence of science teachers SMP/S in Bandung distric. Keywords: Management mentoring and competence